The Role of Performance Management in Improving Employee Performance Effectiveness at PT. Tectona Cipta Niaga - Sam Taufik Kemal Witarsa; Zihan Syentia Mita (Jurnal Manajemen Bisnis dan Pariwisata, 2026)
Performance management is one of the important aspects of human resource management that functions to ensure that employee activities and work results are aligned with organizational goals. This study aims to examine the application of performance management and analyze its contribution to improving the effectiveness of employee performance at PT. Tectona Cipta Niaga. This research uses a descriptive qualitative approach, and collects data through interviews, observations, and documentation. Research shows that companies have implemented a performance management system by setting work targets, supervising the implementation of tasks, evaluating performance regularly, and using ways to give rewards and sanctions. Implementing this system brings benefits both in improving work discipline, work results, quality of outputs, and success in achieving organizational targets. However, companies still face a number of challenges, especially related to differences in employee characteristics, mindsets, and motivation levels that affect the consistency of the implementation of performance management systems. Therefore, it is necessary to evaluate and develop the system on an ongoing basis so that the effectiveness of employee performance can continue to be improved and able to support the achievement of company goals optimally.